Phytochemical analysis of Leptadenia madagascariensis Decne (Apocynaceae) - Andrianarijaona Mamy; Ralaivaon-dratsitonta Jumaël Edith Fabrice; Fatiany Pierre Ruphin; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2025)
Leptadenia madagascariensis Decne, a woody climbing vine endemic to Madagascar, has long been utilized in traditional medicine for its therapeutic properties, despite a lack of detailed scientific investigation. This study was conducted to perform a comprehensive phytochemical analysis of the plant’s aerial parts, thereby contributing to the chemical validation of its ethnobotanical applications and supporting national conservation efforts. The powdered plant material was successively macerated with hexane, dichloromethane (DCM), and methanol, yielding crude extracts with varying polarity. Phytochemical screening of these extracts revealed a significant concentration of polysaccharides, saponins, and steroids. The DCM extract, showing a promising phytochemical profile, was selected for further purification. An initial analysis by thin-layer chromatography (TLC) indicated the presence of four dominant compounds. Subsequent separation using column chromatography resulted in the isolation of a pure compound from fractions 55 to 70. The structure of this isolated compound was determined through a combination of spectroscopic techniques, including mass spectrometry and one-dimensional nuclear magnetic resonance (NMR) spectroscopy (1H NMR, 13C NMR, and DEPT). The spectral data were compared with literature values, leading to the definitive identification of the molecule as β-Sitosterol, a common tetracyclic steroid. This finding confirms the presence of therapeutically valuable steroid compounds in L. madagascariensis, providing a scientific basis for its traditional use and a starting point for further pharmacological research.